2021
DOI: 10.20885/jsb.vol25.iss1.art2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of demographic factors on behavioral biases

Abstract: The purpose of this study was to examine the influence of demographic factors such as gender, age, education, occupation, income, and investment experience on investor behavior bias such as overconfidence bias, disposition effects, herding bias, and mental accounting. This type of research was causal research with a quantitative approach, and the analytical method used was the analysis of SEM (structural equation modeling). This research was conducted by distributing questionnaires to investors listed on the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 26 publications
2
26
1
Order By: Relevance
“…In particular, when they surveyed a group that would soon retire, they found that this group was affected by the overconfidence bias. Beatrice et al (2021), on the other hand, found that education is not related to overconfidence bias, and even if the investor does not have education on capital markets, they can develop themselves with the developing technology. In other words, investors will improve themselves with additional education, increase their knowledge of investment and will not need to make decisions with overconfidence.…”
Section: Investor Demographic Characteristics and Behavioral Biasesmentioning
confidence: 96%
See 4 more Smart Citations
“…In particular, when they surveyed a group that would soon retire, they found that this group was affected by the overconfidence bias. Beatrice et al (2021), on the other hand, found that education is not related to overconfidence bias, and even if the investor does not have education on capital markets, they can develop themselves with the developing technology. In other words, investors will improve themselves with additional education, increase their knowledge of investment and will not need to make decisions with overconfidence.…”
Section: Investor Demographic Characteristics and Behavioral Biasesmentioning
confidence: 96%
“…Regarding gender in terms of bias, it was concluded that women refrain from investing in risky assets and avoid risk, so women are less likely to be affected by the overconfidence bias than men. Beatrice, Murhadi, and Herlambang (2021) also stated that women are less confident and pessimistic than men.…”
Section: Investor Demographic Characteristics and Behavioral Biasesmentioning
confidence: 99%
See 3 more Smart Citations